2022
DOI: 10.1007/s40520-022-02153-5
|View full text |Cite|
|
Sign up to set email alerts
|

High-intensity interval training modulates inflammatory response in Parkinson’s disease

Abstract: Background Recent discoveries show that high-intensity interval training (HIIT) can bring many positive effects such as decreases in fat tissue, lower blood sugar levels, improved learning and memory, and lower risk of cardiac disease. Parkinson’s disease (PD) is a neurodegenerative disorder characterized by loss of the dopaminergic neurons, accompanied by chronic inflammation and neuroinflammation. Previous research shows that interval training can bring a beneficial effect on the inflammation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…For example, performing 8 weeks of HIIT has led to a significant decrease in the serum concentration of tumor necrosis factor-α (TNF-α) and chemerin, and improved body composition and insulin resistance in obese women [ 61 ]. Also, regular HIIT has been shown to reduce TNF-α levels and slow down the progression of Parkinson’s disease by improving serum antioxidant capacity [ 62 ]. In another study, endurance exercise in mice fed a high-fat diet (HFD) caused a significant decrease in the serum levels of fatty acids, ceramides, expression of TNF-α, IL-18, and macrophage inflammatory protein-1γ (MIP-1γ) [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, performing 8 weeks of HIIT has led to a significant decrease in the serum concentration of tumor necrosis factor-α (TNF-α) and chemerin, and improved body composition and insulin resistance in obese women [ 61 ]. Also, regular HIIT has been shown to reduce TNF-α levels and slow down the progression of Parkinson’s disease by improving serum antioxidant capacity [ 62 ]. In another study, endurance exercise in mice fed a high-fat diet (HFD) caused a significant decrease in the serum levels of fatty acids, ceramides, expression of TNF-α, IL-18, and macrophage inflammatory protein-1γ (MIP-1γ) [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sacheli [ 69 ] showed that three months of aerobic cycle training increased ventral striatal dopamine release proportional to fitness improvements in patients with mild-to-moderate PD. Malczynska and colleagues [ 70 ] showed that, in PD, three months of high-intensity interval training exercise increased the synthesis of anti-inflammatory cytokines. The emerging neuroscience evidence described above hints that exercise therapy induces complex adaptive neuroplasticity changes in cortical and basal ganglia circuitries [ 21 , 22 , 71 , 72 , 73 ]…”
Section: Discussionmentioning
confidence: 99%
“…Sacheli [69] showed that three months of aerobic cycle training increased ventral striatal dopamine release proportional to fitness improvements in patients with mild-to-moderate PD. Malczynska and colleagues [70] showed that, in PD, three months of high-intensity interval training exercise increased the synthesis of anti-inflammatory cytokines. The emerging neuroscience evidence described above hints that exercise therapy induces complex adaptive neuroplasticity changes in cortical and basal ganglia circuitries [21,22,[71][72][73] Some authors of the trials included in the present meta-analysis provided vague rationales for BDNF mechanisms (Table 3), including release of intracellular BDNF, secondary to HIIT-associated muscle injuries [54], and exercise-induced, transient hypoxia [53], while no mechanistic explanation was provided by Dicagno et al [51], Frazzitta et al [52], and Freidle et al [55].…”
Section: Exercise Neuroplastic Mechanismsmentioning
confidence: 99%
“…Another study investigated the effects of aerobic exercise training on patients with Parkinson's disease. They noticed that 12 weeks of aerobic exercise training markedly alleviated TNF-α and IL-6 while enhancing IL-10 and IL-10/TNF-α ratio in the serum of patients with Parkinson's disease [ 30 ].…”
Section: Discussionmentioning
confidence: 99%